In Vitro And In Vivo Studies On Antioxidant Potential Of Methanolic Extract Of Pomegranate Fruits (Applied Biological Research, 2017)
The present study was aimed to assess the antioxidant potential of  methanolic extract of pomegranate (Punica granatum) by in vitro assays  and in vivo model. Under in vitro conditions the antioxidant activity of  methanolic extract of pomegranate fruit was 198.3, 192.2, 181.1 and 143.2  mg 100 g-1 by DPPH, nitric oxide, superoxide radical scavenging assays  and ferric reducing antioxidant power assay, respectively. Under in vivo  conditions, the levels of antioxidant enzymes superoxide dismutase,  catalase, glutathione peroxidase were increased and lipid peroxidation  level decreased after supplementation of fresh fruits. The free radical  scavenging and antioxidant activities may be ascribed to the presence of  total polyphenols (148.6 mg 100 g-1), total flavonoids (209.8 mg 100 g-1)  and ascorbic acid content (24.2 mg 100 g-1) in pomegranate fruits. The  results indicate that pomegranate fruit is a potential source of natural  antioxidant.
Keywords: Antioxidant enzyme; lipid peroxidation pomegranate; radical scavenging activity; reducing power